Estratégias de enfrentamento utilizadas por praticantes de Artes Marciais - Souza Júnior, Orlando Marreiro de (2007)
This study objectives to describe the strategies of coping used by practitioners of martial arts; to relate the strategies of coping used by beginning practitioners in martial arts with those used by practitioners with experience; and to relate the strategies of coping to the time of practises of the martial arts. Mens between 15 and 56 years old, most of them were single mens, students till high school, thus distributed: 94 practitioners of Kung Fu Chinese, Kung Fu Vietnamese (Qwan Ki Do), Taekwondo and Karatê similar martial arts of contact technical. They had been distributed in two groups: Group 1 - 67 practitioners with time of practise up to 12 months but they don´t have "black belt" necessary. In this group, there are just teachers and just practitioners and Group 2 - 27 practitioners called beginning, till 12 months of experience. It was used Escala de Modos de Enfrentamento de Problemas: EMEP and a Questionary. The data had been submitted to the Statistical Package will be the Social Science (SPSS), version 15.0 for Windows for descriptive statistical analysis and r-Person. The results had indicated the strategies of coping used by these beginning practitioners or those have black belt. Analyzes showed differences not so important between two groups. In an in agreement understanding the average point of the scale, could be observed that the strategies of coping with "care on problem" and "searching for social support", present a good average of use (steady). It means they use them inside of a standard adjusted in both the groups. It is interesting also to observe about "strategies on the emotion", these are between the observed average minors. The practitioners use these strategies but just a little, denoting more than emotional control in relation to the other strategies. Other important information is that with more time dedicated to Martial Arts teaching, more strategies of social support they develop. Of a logical point of view, this relationship with pupils during teaching helps to better contact social.(AU)